Facades modules for eco-efficient refurbishment of buildings : glazing thermal performance analyses to Coimbra and Faro - Sacht, Helenice Maria (2010)
New legislation and incentives have been created, showing that there is an attempt to act and to intervene in energy efficiency area. Energy consumption reduction and prevention of energy waste is one of the main objectives of the European Union (EU). Building facades constitute a privileged component to propose solutions, once it has a major influence in the energy consumption in the building and in occupants comfort; because it has elements that contribute significantly with the heat transfer. This paper presents a study on about a new facade concept: "Facade Modules for Eco-Efficient Refurbishment of Buildings", especially on thermal performance of glazing modules. Computational simulation was done with the Design Builder software for ten different double glazing types (composed by green and transparent solar control glass, self-cleaning glass, two low-e glasses types, two extra clear glass) for two climates in Portugal (Coimbra and Faro) and four solar orientations (north, south, east and west). The results were obtained for heating and cooling energy necessities and were compared to all glazing types. These results showed a better performance to glazing compositions that combines solar control and self-cleaning glass with extra clear glass to both cities. Facades with green solar control glass and extra clear glass presented a better performance in comparison with others types studied, decrease cooling energy necessities. The great majority of the glass facade compositions presented heating and cooling energy necessities according to Portuguese standards (RCCTE) recommendations.